2020
DOI: 10.3390/ijerph17010298
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol a Exposure, DNA Methylation, and Asthma in Children

Abstract: Epidemiological studies have reported the relationship between bisphenol A (BPA) exposure and increased prevalence of asthma, but the mechanisms remain unclear. Here, we investigated whether BPA exposure and DNA methylation related to asthma in children. We collected urinary and blood samples from 228 children (Childhood Environment and Allergic Diseases Study cohort) aged 3 years. Thirty-three candidate genes potentially interacting with BPA exposure were selected from a toxicogenomics database. DNA methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The DNA methylation levels of 8 CpG sites in cord blood are consistent with those reported in the literature [39,40], and the impact of prenatal BPA exposure on DNA methylation is of great concern. In contrast, previous studies reported that BPA was capable of inducing DNA methylation in both animals [6,41] and humans [15][16][17]40,42]. Hanna et al, (2012) reported that BPA exposure was associated with DNA methylation changes in whole blood using Illumina GoldenGate Methylation Cancer Panel I bead array assays on 1505 CpG sites, in women undergoing ovarian stimulation for in vitro fertilization [15].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The DNA methylation levels of 8 CpG sites in cord blood are consistent with those reported in the literature [39,40], and the impact of prenatal BPA exposure on DNA methylation is of great concern. In contrast, previous studies reported that BPA was capable of inducing DNA methylation in both animals [6,41] and humans [15][16][17]40,42]. Hanna et al, (2012) reported that BPA exposure was associated with DNA methylation changes in whole blood using Illumina GoldenGate Methylation Cancer Panel I bead array assays on 1505 CpG sites, in women undergoing ovarian stimulation for in vitro fertilization [15].…”
Section: Discussionmentioning
confidence: 94%
“…Four animal studies have reported that BPA exposure can provoke intrauterine growth restriction [ 44 ], cause preeclampsia-like features in pregnant mice involved in the reprogramming of DNA methylation of WNT2 (Wnt family member-2) [ 45 ], and cause toxicity in spermatocytes, and DNA methylation may exert an important role in BPA-triggered male reproductive toxicity [ 46 ] and alter the methylation levels of differentially methylated regions (DMRs) including the Snrpn imprinting control region and IGF2R DMR1 [ 47 ]. In addition, three human and epidemiological studies have shown that BPA can cause abnormal development of the central and peripheral nervous system in the fetus [ 48 ], and BPA exposure on children with asthma might operate through the alteration of MAPK1 methylation [ 42 ]. In another epigenome-wide association study on children, being in the high BPA exposure group, compared to the low BPA exposure group, was associated with an increase in DNA methylation of IGF2R [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous association studies have linked BPA and analogs to human reproductive diseases and disorders including increased miscarriage rates ( Sugiura-Ogasawara et al, 2005 , Zbucka-Kretowska et al, 2018 ), low fetal birth weight ( Huo et al, 2015 ), birth defects such as male hypospadias ( Pallotti et al, 2020 ), endometriosis ( Buck Louis et al, 2013 , Simonelli et al, 2017 ), polycystic ovary syndrome ( Rutkowska and Rachon, 2014 ), breast and prostate cancer ( Jenkins et al, 2009 , Moral et al, 2008 , Shafei et al, 2018 , Zhang et al, 2014 ), and precocious puberty ( Leonardi et al, 2017 ), in addition to many neurological, immune, and metabolic disorders ( Robinson and Miller, 2015 , Kardas et al, 2016 , Thongkorn et al, 2019 , Li et al, 2018 , Tewar et al, 2016 , Legeay and Faure, 2017 , Wang et al, 2012 , Wang et al, 2019 , Yang et al, 2020 , Youssef et al, 2018 ). Further, several large studies have reported that in couples undergoing in vitro fertilization (IVF) there were significant correlations between higher urinary BPA concentrations and reduced sperm counts, and abnormal sperm motility and morphology in men, reduced oocyte yield and peak serum estradiol in women, and reduced success with IVF ( Joint and WHO, 2011 , Matuszczak et al, 2019 , Mok-Lin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phthalate exposure could also attenuate the methylation level of TNF-α in whole blood white blood cells and lead to its upregulation, which is an event that increases the risk of asthma in children [89]. The results from another study indicate that exposure to bisphenol A can lead to a decrease in an inflammatory mediator gene MAPK1 methylation in whole blood, provoking childhood asthma [90]. Studies on inner-city children with persistent atopic asthma suggested that persistence in these children was accompanied by promoting the expression of genes related to Th2 immunity.…”
Section: Exposure To Air Pollutants and Chemical Substancesmentioning
confidence: 99%